NiFePd/UiO-66 nanocomposites as highly efficient catalysts to accelerate hydrogen evolution from hydrous hydrazine. Issue 10 (21st August 2019) - Song, Xue; Yang, Pan; Wang, Jingchuan; Zhao, Xiaochong; Zhou, Yuanlin; Li, Yintao; Yang, Lijun
Abstract : NiFe nano-catalysts modified by the dopant of Pd were reducted on UiO-66 by NaBH4, which have been used as a low cost and high efficient catalyst with outstanding activity and durability for hydrogen generation from the decomposition of hydrazine hydrate. Abstract : The exploration of highly efficient catalysts for the hydrolysis of hydrous hydrazine is of great significance for the achievement of future hydrogen economy. In this regard, herein, a catalyst with NiFePd loaded on the metal–organic framework (MOF) UiO-66 was successfully prepared by a simple and safe chemical impregnation method. Due to its high specific surface area, the as-prepared NiFePd/UiO-66 catalyst exhibited efficient catalytic performance for the generation of hydrogen from hydrous hydrazine in an alkaline solution. The results showed that the Ni0.25 Fe0.25 Pd0.5 /UiO-66 catalyst exhibited optimal properties for the decomposition of hydrous hydrazine in an alkaline aqueous solution with a nearly 100% hydrogen selectivity, good activity, and the high total turnover frequency (TOF) value of up to 662.4 h −1 at 80 °C. Moreover, the Ni0.25 Fe0.25 Pd0.5 /UiO-66 catalyst exhibited good durability, which slightly decreased after five cycles of catalytic reaction at 60 °C.